Desenvolvimento e validação de um método analítico indicativo de estabilidade para o ácido nordihidroguaiarético - Santos, Fernanda Carolina Ribeiro dos (2020)
Nordihydroguaiaretic acid is one of the main metabolites produced by Larrea tridentata plant, to which clinical studies have testified its safety and efficacy in therapeutic effects, such as anti-inflammatory and antineoplastic ones. High antioxidant potential is attached to this molecule, because its chemical structure is composed of catechol sheets. Currently, regulatory agencies such as ANVISA and FDA, have determined guidelines to register processes and post-registration of drug therapies. According to such area, analytical methodologies are required to fulfill with norms, such as the resolutions of the collegial board of directors – RDC No 166, 2017 e RDC No 53, 2015. This research aimed at developing and validating an analytical method as a suggestion of stability for nordihydroguaiaretic acid raw material by high performance liquid chromatography. The development was carried out based on initial tests, with optimizations of mobile phase, column, concentration of solutions among others, until the methodology was shown to be validated. Then, the degradation profile of the active was defined according to the forced degradation study that tends to evaluate the analytical method applicability to separate impurities produced after some stress conditions. The conditions were defined based on national and international guides’ recommendations that meet chemical and physical stresses demands. Chemical stresses consisted on exposing samples to the following conditions: hydrolysis in a wide pH range, besides oxidation by metal ions and oxidizing reagent. While, physical degradation conditions consisted on exposing samples to heating, humidity and photodegradation. When the method development was concluded, validation parameters were followed such as: selectivity, linearity, linear range, accuracy, precision (intra- and inter-day) and robustness. The chromatographic system, defined along the development, was in gradient mode using as mobile phase water and methanol with 1.0 mL/min flow, and 3-μl volume injection, 150 mm x 4.6 mm x 5 μm XDB-C18- Agilent Eclipse column, at room temperature and 283-nm detection. The proposed method proved to be selective, since the products from degradation did not interfere on a precise, exact, linear and robust NDGA detection as well as quantification, within the working range. After the successful completion of all analyses concerning the analytical methodology validation, it can be concluded that the proposed method is an indicative of stability to dose NDGA raw matter.